Characteristics of objective daytime sleep among individuals with earthquake-related posttraumatic stress disorder: A pilot community-based polysomnographic and multiple sleep latency test study. (January 2017) - Zhang, Yan; Li, Yun; Zhu, Hongru; Cui, Haofei; Qiu, Changjian; Tang, Xiangdong; Zhang, Wei
Abstract: Little is known about the objective sleep characteristics of patients with posttraumatic stress disorder (PTSD). The present study examines the association between PTSD symptom severity and objective daytime sleep characteristics measured using the Multiple Sleep Latency Test (MSLT) in therapy-naïve patients with earthquake-related PTSD. A total of 23 PTSD patients and 13 trauma-exposed non-PTSD (TEN-PTSD) subjects completed one-night in-lab polysomnography (PSG) followed by a standard MSLT. 8 of the 23 PTSD patients received paroxetine treatment. Compared to the TEN-PTSD subjects, no significant nighttime sleep disturbances were detected by PSG in the subjects with PTSD; however, a shorter mean MSLT value was found in the subjects with PTSD. After adjustment for age, sex, and body mass index, PTSD symptoms, particularly hyperarousal, were found to be independently associated with a shorter MSLT value. Further, the mean MSLT value increased significantly after therapy in PTSD subjects. A shorter MSLT value may be a reliable index of the medical severity of PTSD, while an improvement in MSLT values might also be a reliable marker for evaluating therapeutic efficacy in PTSD patients. Highlights: No significant objective sleep disorders were detected with chronic PTSD subjects. Hyperarousal symptom of PTSD was associated with shorter MSLT values. Shorter MSLT value may be a reliable index for evaluating the severity of PTSD.